ABSENTEEISM ONLINE SYSTEM FOR HEAD OFFICE AND ADMINISTRATIVE EMPLOYEES BETWEEN BRANCH LKBN - Permata Sari; Sahni D Purba, Skom, MM (Jurnal Sistem Informasi, 2001)
High performance from every employee in a company is required to support the activities and operations at the company. The indicator used by the personnel in assessing the performance of the employee of one of them is the presence or absence of employees. From manual administrative systems, there were many shortcomings and limitations of personnel and HRD to be able to assess employee discipline and activeness. Making the new system, for replacing the existing system is expected to assist the personnel and HRD. The first thing to do is replace the old machine with the absence of new attendance machines, to support the communication with the computer, as well as revamping the local network system and network system linking the headquarters and branch offices.